Application of molecularly imprinted polymers for the solid-phase extraction of hexanitrohexaazaisowurtzitane (CL-20) from soil samples. Issue 22 (20th May 2016) - Wang, Jian; Xue, Min; Meng, Zihui; Xu, Zhibin; Luo, Jun
Abstract : Eight molecularly imprinted polymers (MIPs) for CL-20 were synthesized by precipitation polymerization in acetonitrile. Abstract : Eight molecularly imprinted polymers (MIPs) for CL-20 were synthesized by precipitation polymerization in acetonitrile. The amounts and types of functional monomers and crosslinkers and the polymerization temperature were taken into account. The imprinting effect and selectivity of the MIPs were evaluated by static adsorption experiments. The results showed that the MIPs prepared at 4 °C had a better imprinting effect. MIP 4, which was prepared with acrylamide (AAm) as the functional monomer and ethyleneglycol dimethacrylate (EGDMA) as the crosslinker, was the optimal MIP. When the molar ratio of the template (CL-20), functional monomer and crosslinker was 1/6/24, the MIP possessed optimal absorbability and selectivity. Its specificity parameter (SP) to TADB, HMX and RDX was 15.27, 17.66 and 15.05, respectively. The binding capacity ( Q max ) of MIP 4 for CL-20 was 115.7 μg g −1 and the adsorption reached equilibration within 10 min. MIP 4 as a selective sorbent was used to extract CL-20, using SPE from the mixed solution of its precursor compound, its analogues and soil samples. Acetonitrile was used as a sample solvent, and methanol was used as a washing solvent. Then CL-20 was successively eluted with acetonitrile and methanol/acetic acid (4/1, v/v), and the recovery of CL-20 was 95%. After 5 SPE cycles, the extraction ability of the cartridge for soil samples did not decrease obviously.